Dynamical Behavior of Some Recursive Exponential Difference Equations
In this paper, we study boundedness, persistence and rate of convergence of system of difference equations of exponential form r_n+1=λ +e^-(μ r_n+ξ s_n) δ +μ r_n+ξ s_n , s_n+1=λ +e^-(μ s_n+ξ t_n) δ +μ s_n+ξ t_n , t_n+1=λ +e^-(μ t_n+ξ r_n) δ +μ t_n+ξ r_n , where n=0, 1, 2,… and λ , μ , ξ and δ are non-negative constants and the initial conditions r_0, s_0, t_0 are non-negative real values., number=3, journal=Journal of Applied Nonlinear Dynamics, author=Khaliq, Abdul and Shabbir, Muhammad and Zubair, Muhammad and Rohail, Muhammad and Sadiq, Stephen, year=2026, month=Aug., pages=533–548